PENTINGNYA PENDIDIKAN DALAM RANGKA MEMBANGUN MOTIVASI PELAJAR UNTUK MELANJUTKAN KE JENJANG PERGURUAN TINGGI - Zaidah, Alpi; Hidayatulloh, Alpiana; Mahariyanti, Ermila; Irwansah, Irwansah; Prayunisa, Fena; Azizi, Asrorul; Rasyidi, Mulia; Muttaqin, Muh. Zaini Hasanul; Muhsinun, Muhsinun (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
The purpose of this service is to provide students with knowledge about the importance of education to motivate students to continue to the university level. The implementation of this activity was carried out at MA Mu'allimat NW Pancor class XII IPA / IPS with as many as 50 people. The method used in this service activity is socialization with lectures accompanied by material exposure regarding the importance of education, introduction to universities, prospects for college graduates, and educational assistance, and ends with a question and answer session. The results of this service are based on the enthusiasm of the participants, and warm interaction in discussions, and can change the mindset of students towards higher education and the emergence of student motivation in continuing their education to the college level.